2014
DOI: 10.3109/0142159x.2014.887833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two case-based learning conditions with real patients in teaching occupational medicine

Abstract: Both approaches with augmented interaction in 2011 and 2012, improved performance and satisfaction among students. However, students valued the use of real patients higher than paper-form cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Only a few studies have assessed changes in the attitudes of medical students towards Occupational Medicine/Occupational Health, a subject that some European medical schools do not include at all, or if they do, only several hours are devoted to this subject [ 8 , 12 ]. In line with our results, some previous studies have shown an improvement in students’ attitudes towards and competencies in Occupational Medicine when various learning methods, including case studies, small-group learning, interactive large-group teaching, field activities and e-learning, were applied [ 15 , 16 , 17 ] or when blended learning was applied but in the subject of Family Medicine [ 13 ]. Conversely, in the field of Occupational Medicine but among Physiotherapy students, the study of Eckler et al did not offer a general recommendation favoring either the classical setting or blended learning for improving cognitive learning outcomes, although students’ self-reports on the affective domain indicated a preference for blended learning [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies have assessed changes in the attitudes of medical students towards Occupational Medicine/Occupational Health, a subject that some European medical schools do not include at all, or if they do, only several hours are devoted to this subject [ 8 , 12 ]. In line with our results, some previous studies have shown an improvement in students’ attitudes towards and competencies in Occupational Medicine when various learning methods, including case studies, small-group learning, interactive large-group teaching, field activities and e-learning, were applied [ 15 , 16 , 17 ] or when blended learning was applied but in the subject of Family Medicine [ 13 ]. Conversely, in the field of Occupational Medicine but among Physiotherapy students, the study of Eckler et al did not offer a general recommendation favoring either the classical setting or blended learning for improving cognitive learning outcomes, although students’ self-reports on the affective domain indicated a preference for blended learning [ 18 ].…”
Section: Discussionsupporting
confidence: 91%
“…CBL is used to impart knowledge in various fields in health care and various fields of medicine. The findings in this review showed that articles demonstrated the use of CBL in medicine, 2 , 4 7 , 9 , 10 , 12 14 , 18 21 , 24 26 , 30 , 33 , 34 , 36 , 37 , 39 44 , 46 , 48 62 , 64 67 dentistry, 8 , 15 , 16 , 22 , 23 , 28 pharmacology, 11 , 27 , 29 , 35 , 45 , 63 occupational and physical therapy, 31 ...…”
Section: Discussion and Reviewmentioning
confidence: 79%
“…Ważnym elementem tej metody jest samodzielność w podejmowaniu decyzji, dzięki czemu szkolący się mogą rozwijać cenne umiejętności, pokazywać swoje mocne strony oraz odkrywać własne zdolności i predyspozycje. Z pojęciem nauczania problemowego związane jest pokrewne mu pojęcie nauczania opartego na przykładach (Case Based Learning, CBL), które w założeniu korzysta z przykładów z życia, czyniąc dydaktykę bardziej rzeczywistą [18,[20][21][22][23][24][25][26]. CBL jest definiowane jako ustrukturyzowane doświadczenie edukacyjne, w którym wykorzystuje się realistyczne przypadki kliniczne w celu rozwiązania lub zbadania problemu klinicznego [25,26].…”
Section: Wstępunclassified